KARAKTERISASI PENGARUH KECEPATAN LAS PADA PENGELASAN MIG AA5083H116 DENGAN ELEKTRODA ER5356 - Mudjijana Mudjijana; Moch. Noer Ilman; Priyo Tri Iswanto (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
Abstract. Indonesia is a maritime country where 2/3 of its territory is ocean. Therefore, many ships are needed for transportation from one island to the nother within NKRI region. The AA5083H116 materials are widely used in maritime transportation vehicle due to its low density and high weldability. The research propose is to characterize the influence of welding speed of Metal Inert Gas (MIG) of AA5083H116 using ER5356 electrode on the welded joint properties. The AA5083H116 materials of 3 mm x 1200 mm x 2400 mm dimension were cut into welding specimens of 3 mm x 75 mm x 300 mm size. Any pair of specimens was welded using electrode of 0.8 mm diameter. The welding parameters being used are 19 volts of electrical voltage, 120 amperes of electrical current, and 8, 10, 12 mm/s of welding speeds. The characterization were carried out on angle distortion that measured using dial indicator on a milling machine table, X-ray radiography test, as well as physical and mechanical properties tests i.e. microstructure, Vickers micro hardness, tensile and bending strength. The research results show that the smallest distortion angle was found at welding speed of 12 mm/s, all of the welding results satisfy the distortion angle of < 5o, and the radiographic results satisfy the DEPNAKER RI regulation standard. The microstructure exhibits Al2Mg3 precipitation, Vickers hardness distributions, while the highest tensile and bending strength were obtained at welding speed of 10 mm/s.